Measuring Ontological Simplicity - NOËL SAENZ (Ergo, An Open Access Journal of Philosophy)
Standard approaches to ontological simplicity focus either on the number of things or types a theory posits or on the number of fundamental things or types a theory posits. In this paper, I suggest a ground-theoretic approach that focuses on the number of something else. After getting clear on what this approach amounts to, I motivate it, defend it, and complete it.